{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

AEM_3e_Chapter04

# AEM_3e_Chapter04 - 4 1{f(t = The Laplace Transform...

This preview shows pages 1–4. Sign up to view the full content.

4 4 The Laplace Transform EXERCISES 4.1 Definition of the Laplace Transform 1. { f ( t ) } = 1 0 e st dt + 1 e st dt = 1 s e st 1 0 1 s e st 1 = 1 s e s 1 s 0 1 s e s = 2 s e s 1 s , s > 0 2. { f ( t ) } = 2 0 4 e st dt = 4 s e st 2 0 = 4 s ( e 2 s 1) , s > 0 3. { f ( t ) } = 1 0 te st dt + 1 e st dt = 1 s te st 1 s 2 e st 1 0 1 s e st 1 = 1 s e s 1 s 2 e s 0 1 s 2 1 s (0 e s ) = 1 s 2 (1 e s ) , s > 0 4. { f ( t ) } = 1 0 (2 t + 1) e st dt = 2 s te st 2 s 2 e st 1 s e st 1 0 = 2 s e s 2 s 2 e s 1 s e s 0 2 s 2 1 s = 1 s (1 3 e s ) + 2 s 2 (1 e s ) , s > 0 5. { f ( t ) } = π 0 (sin t ) e st dt = s s 2 + 1 e st sin t 1 s 2 + 1 e st cos t π 0 = 0 + 1 s 2 + 1 e πs 0 1 s 2 + 1 = 1 s 2 + 1 ( e πs + 1) , s > 0 6. { f ( t ) } = π/ 2 (cos t ) e st dt = s s 2 + 1 e st cos t + 1 s 2 + 1 e st sin t π/ 2 = 0 0 + 1 s 2 + 1 e πs/ 2 = 1 s 2 + 1 e πs/ 2 , s > 0 7. f ( t ) = 0 , 0 < t < 1 t, t > 1 { f ( t ) } = 1 te st dt = 1 s te st 1 s 2 e st 1 = 1 s e s + 1 s 2 e s , s > 0 8. f ( t ) = 0 , 0 < t < 1 2 t 2 , t > 1 { f ( t ) } = 2 1 ( t 1) e st dt = 2 1 s ( t 1) e st 1 s 2 e st 1 = 2 s 2 e s , s > 0 198

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
4.1 Definition of the Laplace Transform 9. The function is f ( t ) = 1 t, 0 < t < 1 0 , t > 1 so { f ( t ) } = 1 0 (1 t ) e st dt + 1 0 e st dt = 1 0 (1 t ) e st dt = 1 s (1 t ) e st + 1 s 2 e st 1 0 = 1 s 2 e s + 1 s 1 s 2 , s > 0 10. f ( t ) = 0 , 0 < t < a c, a < t < b 0 , t > b ; { f ( t ) } = b a ce st dt = c s e st b a = c s ( e sa e sb ), s > 0 11. { f ( t ) } = 0 e t +7 e st dt = e 7 0 e (1 s ) t dt = e 7 1 s e (1 s ) t 0 = 0 e 7 1 s = e 7 s 1 , s > 1 12. { f ( t ) } = 0 e 2 t 5 e st dt = e 5 0 e ( s +2) t dt = e 5 s + 2 e ( s +2) t 0 = e 5 s + 2 , s > 2 13. { f ( t ) } = 0 te 4 t e st dt = 0 te (4 s ) t dt = 1 4 s te (4 s ) t 1 (4 s ) 2 e (4 s ) t 0 = 1 (4 s ) 2 , s > 4 14. { f ( t ) } = 0 t 2 e 2 t e st dt = 0 t 2 e ( s +2) t dt = 1 s + 2 t 2 e ( s +2) t 2 ( s + 2) 2 te ( s +2) t 2 ( s + 2) 3 e ( s +2) t 0 = 2 ( s + 2) 3 , s > 2 15. { f ( t ) } = 0 e t (sin t ) e st dt = 0 (sin t ) e ( s +1) t dt = ( s + 1) ( s + 1) 2 + 1 e ( s +1) t sin t 1 ( s + 1) 2 + 1 e ( s +1) t cos t 0 = 1 ( s + 1) 2 + 1 = 1 s 2 + 2 s + 2 , s > 1 16. { f ( t ) } = 0 e t (cos t ) e st dt = 0 (cos t ) e (1 s ) t dt = 1 s (1 s ) 2 + 1 e (1 s ) t cos t + 1 (1 s ) 2 + 1 e (1 s ) t sin t 0 = 1 s (1 s ) 2 + 1 = s 1 s 2 2 s + 2 , s > 1 17. { f ( t ) } = 0 t (cos t ) e st dt = st s 2 + 1 s 2 1 ( s 2 + 1) 2 (cos t ) e st + t s 2 + 1 + 2 s ( s 2 + 1) 2 (sin t ) e st 0 = s 2 1 ( s 2 + 1) 2 , s > 0 199
4.1 Definition of the Laplace Transform 18. { f ( t ) } = 0 t (sin t ) e st dt = t s 2 + 1 2 s ( s 2 + 1) 2 (cos t ) e st st s 2 + 1 + s 2 1 ( s 2 + 1) 2 (sin t ) e st 0 = 2 s ( s 2 + 1) 2 , s > 0 19. { 2 t 4 } = 2 4! s 5 20. { t 5 } = 5!

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### Page1 / 54

AEM_3e_Chapter04 - 4 1{f(t = The Laplace Transform...

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online